A Combination of Low Doses of Fluvastatin and Valsartan Decreases Arterial Stiffness in Patients After Myocardial Infarction: A Pilot Study - Jurij Hanžel; Žiga Piletič, MD; Martina Turk, MD; Barbara Eržen, MD, PhD; Mišo Šabovič, MD, PhD (Current Therapeutic Research, 2015)
Background: Despite optimum treatment, patients who experience myocardial infarction are still at high risk for future events. Objective: We evaluated the effect of 30 days of treatment with combination of low, subtherapeutic doses of fluvastatin and valsartan on arterial stiffness in patients after myocardial infarction, a therapy that has not been used yet. Methods: Fourteen male patients with a history of myocardial infarction were enrolled into a pilot double-blind randomized controlled study. They were allocated to receive 10 mg fluvastatin and 20 mg valsartan or placebo for 30 days in addition to their regular pharmacotherapy. Carotid–femoral pulse wave velocity was measured on inclusion, after 30 days, and after 3 months. Results: Mean (SD) carotid–femoral pulse wave velocity decreased significantly in the treatment group after 30 days and persisted at lower values after 3 months (from 8.4 [1.5] m/sec to 7.3 [1.1] m/sec to 7.2 [0.8] m/sec; P < 0.05). The 95% CI for decrease after 30 days in the treatment group was 0.5–1.6. Only nonsignificant changes were observed in the control group. Serum lipid levels and arterial blood pressure did not change significantly in any group. Conclusions: The treatment resulted in a significant and sustained improvement of arterial stiffness in male patients with a history of myocardial infarction, which highlights the need for further study of this new approach.